2020
DOI: 10.1292/jvms.19-0439
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and clinicopathological features and outcomes of Miniature Dachshunds with bone marrow disorders

Abstract: Non-neoplastic bone marrow disorders such as non-regenerative immune-mediated anemia, pure red cell aplasia, and myelodysplastic syndrome are major causes of nonregenerative anemia in dogs. However, there has been no study on the clinical and clinicopathological features of canine non-neoplastic bone marrow disorders in Japan. Hence, we first investigated the breed disposition of non-neoplastic bone marrow disorders that induce anemia as a retrospective study and found that Miniature Dachshund (MD) was a predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Therefore, the available evidence regarding the detailed clinicopathologic findings and clinical course of the disease is insufficient. Interestingly, recent studies have indicated that the Miniature Dachshund (MD) breed is predisposed to non-neoplastic bone marrow (BM) diseases that induce non-regenerative anemia [ 2 , 17 ]. Cases of immunosuppressive treatment-resistant MDs with anemia frequently occur in Japan; however, the cause and pathophysiology of such cases have not been clarified yet.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the available evidence regarding the detailed clinicopathologic findings and clinical course of the disease is insufficient. Interestingly, recent studies have indicated that the Miniature Dachshund (MD) breed is predisposed to non-neoplastic bone marrow (BM) diseases that induce non-regenerative anemia [ 2 , 17 ]. Cases of immunosuppressive treatment-resistant MDs with anemia frequently occur in Japan; however, the cause and pathophysiology of such cases have not been clarified yet.…”
mentioning
confidence: 99%
“…Cases of immunosuppressive treatment-resistant MDs with anemia frequently occur in Japan; however, the cause and pathophysiology of such cases have not been clarified yet. Furthermore, there is currently no report of a case of an MD with HPS-IMHA and non-regenerative anemia [ 17 ]. In this report, we describe the clinicopathological findings and clinical courses of the cases of two MDs with HPS-IMHA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Case 5 demonstrated nonregenerative anemia, and other causes of nonregenerative anemia were ruled out. The fact that the dog was a miniature dachshund, a breed predisposed to NRIMA in Japan ( Tani et al., 2020 ), increased the likelihood of NRIMA.…”
Section: Discussionmentioning
confidence: 99%
“…Nonregenerative anemia is a relatively common condition in dogs, with known causes including inflammatory diseases, chronic renal disease, nutritional anemia, or bone marrow diseases. Among them, pure red cell anemia (PRCA) and nonregenerative immune-mediated anemia (NRIMA) are the most common bone marrow diseases ( Weiss, 2006 ), especially in Japan where the incidence of NRIMA in miniature dachshunds is very high ( Tani, Tomiyasu, Ohmi, Ohno & Tsujimoto, 2020 ). PRCA is thought to be caused by a lack of erythroblast progenitor cells, whereas NRIMA is thought to be caused by phagocytosis and abnormal differentiation of erythroblasts in the bone marrow ( Weiss, 2008 ; Woolhead, Szladovits, Chan, Swann & Glanemann, 2021 ).…”
Section: Introductionmentioning
confidence: 99%